2000
DOI: 10.1038/sj.bmt.1702334
|View full text |Cite
|
Sign up to set email alerts
|

GVHD dry eyes treated with autologous serum tears

Abstract: Summary:Two cases of GVHD with severe dry eyes are reported where conventional therapy failed to control ocular signs and symptoms. Autologous serum tears, however, resulted in a beneficial clinical effect with marked attenuation of the symptoms. This therapy proved to be safe during 10 months of treatment. Bone Marrow Transplantation (2000) 25, 1101-1103. Keywords: GVHD; dry eye; autologous serum tears; allogeneic PBPC transplantation The treatment of ocular disorders with biological fluids has long been advo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 6 publications
2
76
0
4
Order By: Relevance
“…For more symptomatic patients, cyclosporine and/or steroid eye drop may be used, but cyclosporine eye drop may irritate the eyes. Eye drops made of autologous serum has been tried and very effective in some cases [159]. Scleral contact lenses, a large size contact lens which rests on sclera and creates a tear-filled vault over the cornea, may help in refractory cases.…”
Section: Eye Gvhdmentioning
confidence: 99%
“…For more symptomatic patients, cyclosporine and/or steroid eye drop may be used, but cyclosporine eye drop may irritate the eyes. Eye drops made of autologous serum has been tried and very effective in some cases [159]. Scleral contact lenses, a large size contact lens which rests on sclera and creates a tear-filled vault over the cornea, may help in refractory cases.…”
Section: Eye Gvhdmentioning
confidence: 99%
“…Dry eye is one of the major symptoms of cGVHD. 1,2 Although several therapies have been used to minimize the symptoms of dry eyes associated with cGVHD, [3][4][5] an effective treatment has not been established.…”
mentioning
confidence: 99%
“…10 Patients have reported that the duration of symptomatic relief from serum tears is longer than artificial tears. 11 The rationale for treatment is based on the fact that vitamins and growth factors found in tears are also found in serum.…”
Section: Commentmentioning
confidence: 99%
“…Autologous serum tears have been successfully used in the treatment of dry eye secondary to Sjogren's syndrome, cicatricial pemphigoid, Stevens-Johnson syndrome, and superior limbic keratitis. 12 Local variations in strength (20-100%) 10,12 and preparation of autologous serum tears exist. In our patient, a strength of 100% was used, made from 60 ml clotted blood centrifuged at 2000 revs/min for 5-10 min.…”
Section: Commentmentioning
confidence: 99%